Social and Economic Aspects of the EU 's Education Policy - Zuzana Horváthová; Andrea Čajková (National Research Mordova State University, 2018)
Introduction. The issue of education policy is very topical throughout the entire spectrum of society and undoubtedly throughout the European space. At the same time, this policy must be taken into account in any period of a civilized human history. By investing in education, we invest in the human population and participate in the formation of future generations. This article aims to study and analyse the current state of implementation of innovative approaches to the development of education and EU education policy, to identify the key aspects of the EU Education Policy at the present time. We focus mainly on the analysis of the range of the process of implementation of the Strategy Europe 2020 in this field with the particular impact on incorporation of new approaches into the current education policy system as such in the modern 21st century education system based on determining the tools necessary to implement the key strateg ies. Materials and Methods. The authors address individual approaches of the EU Member States in the field of the education and education policy, which can be beneficial for later incorporation of improving innovations into national education systems using the traditional methods of empirical analysis as description and classification, induction and deduction, content analysis, comparison and syntheses. The empirical basis of this study includes the results of a secondary analysis of the research da ta covering the problems of education policies. Results. There is a pragmatic focus on the issue of education in society, which also results, in terms of the macroeconomic indicators, in raising the standard of living of the population. Based on our conclusions, where we identified the real need of in-depth analysis of the situation in the education sector and a strategy to achieve effective change in mainstream educational thinking, policy and practice. We should not only determine where the sector is at present, but also engage as many institutions as possible in the review process, making sure that it is driven by their needs and to set key determinants of the education policies of the individual Member States in order to achieve the EU 's objectives in terms of education, competitiveness and social cohesion. The results of the study have practical significance: the mechanisms can be reproduced in the field of defining the instruments of the harmonization in the EU education policy with the competences of the Member States. Discussion and Conclusions. The attention is drawn to the socio-economic context that affects the education policy, and despite the pursuit for a kind of harmonization in the EU , the education policy remains substantially within the competence of the Member States. Our results suggest that the use of integrative mechanisms allows to improve the efficiency of EU education policy and at the same time the Member States education policies. The main directions for further research in this field and questions for discussion and another positive move remain: what are the challenges facing education policies EU and Member States in the context of globalisation, the expansion of the European Union and the imperative of sustainable development.